The Impact of Infection Prevention Bundles on Neurosurgical Outcomes and Healthcare Costs: A Systematic Review - Putra, Fajar Faisal; Akhmad Imron; Muhammad Adam Pribadi (HM Publisher, 2024)
Background: Post-operative infections represent a significant challenge in neurosurgery, leading to increased morbidity, mortality, and healthcare costs. The implementation of infection prevention bundles, which encompass a set of evidence-based practices, has emerged as a potential solution to mitigate these adverse outcomes. This systematic review aims to evaluate the effectiveness of infection prevention bundles in improving neurosurgical outcomes and reducing healthcare costs. Methods: A comprehensive search of electronic databases (PubMed, Scopus, Web of Science) was conducted to identify studies published between 2010 and 2023 that evaluated the impact of infection prevention bundles on neurosurgical outcomes and healthcare costs. The search strategy included keywords such as